Analisis Implementasi Pendidikan dan Pelatihan Human Capital di Industri Kreatif - Windi Octaviani; Gustina Sari; Diva Alnaya; Putri Kemala Dewi (Masyarakat Ekonomi Syariah Bogor, 2024)
Creative industries play an important role in the global economy, and the development of high-quality human resources is essential to drive innovation and productivity. The purpose of this study is to analyze the status of the implementation of human resource development and training in the creative industry. Using a qualitative approach, data was collected through in-depth interviews with industry players, academics, and policy makers, as well as analysis of related documents. The results showed that the combination of formal and non-formal education, cooperation between industry and educational institutions, and the use of modern technology play an important role in the development of human resources. Although formal education provides a solid theoretical foundation, non-formal education and technologies such as e-learning and VR can help improve certain practical skills according to market needs. . Collaboration between industry and educational institutions ensures relevant curricula and valuable practical experience for learners. Despite challenges such as limited resources and rapid technological change, effective education and training can enhance the competitiveness and growth of creative industries.